Effect of Melatonin Implants on Sexual Behavior and Testosterone in Awassi Rams - AL-Shammary, Salah Mahdi; A., Al-Yasiri E. (Diyala Journal for Veterinary Sciences, 2023)
Aims: to detect the influence of melatonin implants during different season on sexual behavior and testosterone concentrations in Awassi rams. Methods: Fifteen adult Awassi rams were divided in to two groups randomly ,control group and treated group (melatonin implants 54 mg). Each ram was given a twenty-minute test period to assess its sexual behavior. In order to determine the levels of testosterone, blood samples from rams were taken every month during the experiment. Results: In every season, the control group’s reaction time values were considerably high significant ( P 0.05) than the treated group. In the spring, the amount of ejaculated in the treatment group was substantially higher (P 0.05) than in the control group. In the summer, the treated group’s testosterone levels were considerably (P 0.05) greater than the control group. Conclusions: Treatment with melatonin implants improved the sexual behavior and testosterone level of Awassi rams during different season.